DNA topoisomerase II must act at mitosis to prevent nondisjunction and chromosome breakage. - Holm, C (1989)
The hypothesis that DNA topoisomerase II facilitates the separation of replicated sister chromatids was tested by examining the consequences of chromosome segregation in the absence of topoisomerase II activity. We observed a substantial elevation in the rate of nondisjunction in top2/top2 cells incubated at the restrictive temperature for one generation time. In contrast, only a minor increase in the amount of chromosome breakage was observed by either physical or genetic assays. These results suggest that aneuploidy is a major cause of the nonviability observed when top2 cells undergo mitosis at the restrictive temperature. In related experiments, we determined that topoisomerase II must act specifically during mitosis. This latter observation is consistent with the hypothesis that the mitotic spindle is necessary to allow topoisomerase II to complete the untangling of sister chromatids.